THE TRANSFORMATION OF THE EVANGELICAL CHURCH OF VIETNAM AND THE TORAJA CHURCH IN INDONESIA TOWARD WOMEN-INCLUSIVE LEADERSHIP: CULTURAL, POLITICAL AND RELIGIOUS CONTEXTS - and Jeanny Dhewayani, Le Ngoc Bich Ly, Wening Udasmoro, (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2017)
This paper starts with the question: Why do Protestant churches in Asia have different levels of accommodating women in leadership? By taking two case studies - the Evangelical Church of Vietnam (ECVN) and the Toraja Church in Indonesia that have similar starting points but different levels of transformation regarding women’s leadership, the paper aims to explore how the cultural, political, and religious contexts of these churches are different and how they contribute to the different process of church transformation toward women-inclusive leadership based on both primary and secondary data. Keywords: Women in Leadership, The Evengelical Church of Vietnam, Toraja Church